Full-thickness macular hole formation following anti-VEGF injections for neovascular age-related macular degeneration - Kabanarou SA (Dove Medical Press, 2017)
Stamatina A Kabanarou,1 Tina Xirou,1 George Mangouritsas,1 Christina Garnavou-Xirou,2 Eirini Boutouri,1 Ilias Gkizis,1 Irini Chatziralli3 1Retina Department, Korgialeneio Benakeio, Hellenic Red Cross Hospital, Athens, Greece; 2Retina Department, King’s College Hospital, London, UK; 32nd Department of Ophthalmology, University of Athens, Athens, Greece Purpose: Macular hole (MH) is part of a group of age-related degenerative diseases characterized by pathology of vitreomacular interface. Similarly, neovascular age-related macular degeneration (nAMD) affects older patients and is a leading cause of irreversible visual loss. The purpose of this case series is to describe the development of full-thickness MH in patients with nAMD, following antivascular endothelial growth factor (anti-VEGF) treatment.Methods: Participants in this case series were four patients with nAMD, who received anti-VEGF injections with variable therapeutic response to treatment. Patients were examined at baseline (when AMD was diagnosed) and monthly thereafter. The examination included visual acuity measurement, slit-lamp biomicroscopy, and optical coherence tomography.Results: All patients were found to develop full-thickness MH within 1–4 months after the last anti-VEGF injection, even in the absence of pre-existing vitreomacular interface abnormalities in some cases. The median number of injections before the MH formation was 3.Conclusion: MH formation may represent an adverse effect of anti-VEGF treatment in patients with nAMD and could be also coexisting pathology with nAMD in older individuals. Keywords: macular hole, age-related macular degeneration, anti-VEGF